Effects of Chronic Factor VIII Substitution on Immune Parameters in HIV Seronegative Haemophiliacs: a Comparison between Cryoprecipitate and Factor VIII Concentrate - Allersmaa, D P; Smld, W M; van der Does, J A; van der Meer, J; Briët, E (Thrombosis and Haemostasis, 1996)
Chronic substitution therapy of HIV-negative haemophiliacs with factor VIII products can result in abnormalities of ex-vivo measured immune parameters. To assess a possible relation between these abnormalities and product purity, we analyzed two groups of HIV-negative HCV-positive haemophiliacs, one treated with cryoprecipitate exclusively, the other with more purified factor VIII concentrates. Compared to age matched non-transfused male controls, increased numbers of white cells, granulocytes, IgG and IgM levels and decreased CD4+/CD8+ ratios were found in both patient groups. In the concentrate receivers, the numbers of mononuclear cells, CD4+, CD8+ and CD3+/HLA-DR+ cells indicating activated T-cells, were higher than in the cryoprecipitate group. In conclusion, both cryoprecipitate and intermediate/high purity concentrate recipients showed immune parameter abnormalities. These abnormalities tended to be somewhat more pronounced in patients treated with concentrates. By now there is no indication of the clinical relevance of the abnormalities in previously treated HIV seronegative haemophiliacs.